Spectres of Marxism: A Comment on Mike Savage's Market Model of Class Difference. Issue 2 (May 2015) - Toscano, Alberto; Woodcock, Jamie
This article is a critique of Mike Savage's 'From the "problematic of the proletariat" to a class analysis of the "wealth elites"'. It first rejects the notion of the 'problematic of the proletariat' – the importance of a dividing line between the working and middle class – instead situating the argument within contemporary debates on class analysis. The critique introduces the broader context of neoliberalism and financialization, alongside a consideration of class globally. It stresses the importance of exploitation for understanding class and inequality, rather than moving to the notion of 'advantage', as proposed by Savage, which expels an understanding of power. While the focus on elites in class analysis is welcomed, it is argued that there is a continuing interdependence between classes and that race and gender must also be considered.